Kata panggilan dalam komuniti Bahasa Melayu Sambas di Kalimantan Barat: Sistem dan konteks / Endang Susilawati - Endang , Susilawati (2016)
Address terms in a speech community are represented in various linguistic forms with their particular rules of usage which are usually in accordance with the system of socio-cultural of the community. Within the context various speech situations and events, the usage becomes dynamic. This research is about the system of address in Sambas Malay speech community which was conducted for three purposes. Firstly, to identify the system of address in Sambas Malay speech community within the situation of kinship and intimate social relationship based on the componential analysis. Secondly, to analyse the system of address in the community within the situation of kinship and intimate social relationship based on contextual analysis. Thirdly, to interprete how the system of address is interrelated to the socio-cultural system of the community. The ethnography of communication approach was implemented in the collection of data in the field, specifically applying both participant and non-participant observation techniques. Simultaneously, unstructured interview and conversation voice recording were also applied. Beside these, the transcriptions of some relevant dialogues of locally produced films were also selected to confirm how the address forms were contextually used. As for the analyses of the data, two models have been applied. The first is the componential analysis and the second is the contextual model of analysis, following the ethnography of speaking model of Dell Hymes. The findings of the research are as follows: Firstly, the address forms in Sambas Malay speech community take various kinds of linguistic forms, including personal names, second person pronouns, common nouns, kinterms, various reference terms of social status, titles, and epithets. Based on the componential analysis, the determining factors in the choice of a particular term is determined by the role relationship between the two interactants; gender and age of the addressee as well his/her social status and ethnic background identity. This system of usage generate rules of mutual reciprocity and non-mutual reciprocity and rules of alternation. Besides, individual interest or choice is another rule of alternation in address form usage. To some extent, these rules have extended some implicit meaning called social meanings. They are not only limited to power and solidarity but also include the meaning of kinship relation, social distance, intimacy and politeness. Secondly, the usage of address forms in context shows their dynamicity. In general, the formality or the non-formality of the communicative events influence the choice of the address forms. At the same time, other communicative components (SPEAKING) also influence the usage. This system of usage has implied some more extended social meanings in addition to the ones already existed. They include the meanings of formality or unformality, awareness of one’s ethnic background of identity, respect or deference, endearment, disappointment, and language appropriateness (berbudi bahasa) as well as teasing or mocking. Finally, all the forms of address represent the system of sociocultural values in Sambas Malay speech community.